2005
DOI: 10.1017/s146114570500581x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and long-term effects of a single dose of MDMA on aggression in Dark Agouti rats

Abstract: MDMA causes selective depletion of serotonergic terminals in experimental animals and the consequent decrease in synaptic 5-HT may, inter alia, increase impulsivity. To study the effects of MDMA upon brain function, the behaviour of male Dark Agouti rats exposed to MDMA (15 mg/kg i.p.), two 5-HT1B agonists (CGS-12066A and CP-94,253, both 5 mg/kg i.p.) or saline were investigated in the resident-intruder test. Studies were performed in drug-naive rats and also in rats exposed to MDMA (15 mg/kg i.p.) 21 d earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
7
9
0
Order By: Relevance
“…However, the same studies showed that aggressive mood was elevated during the mid-week period following a weekend of Ecstasy use, a phenomenon that could be related to MDMA-induced depletion of 5-HT (Krakowski, 2003;Miczek et al, 2002). In accordance with the human literature, rats given relatively low doses of MDMA showed increased social interaction and decreased aggressive behavior while the drug is still 'on board' (Morley and McGregor, 2000), whereas 5-HT-depleting doses of MDMA produced later increases in aggressiveness in the social interaction test (Ando et al, 2006), though not in the resident-intruder paradigm (Kirilly et al, 2005). When the social interaction test was carried out in the present study, many of the control (SAL/SAL) rats fought when confronted with an unfamiliar male, whereas the animals in the SAL/MDMA group unexpectedly showed significantly less of this behavior.…”
Section: Discussionsupporting
confidence: 55%
“…However, the same studies showed that aggressive mood was elevated during the mid-week period following a weekend of Ecstasy use, a phenomenon that could be related to MDMA-induced depletion of 5-HT (Krakowski, 2003;Miczek et al, 2002). In accordance with the human literature, rats given relatively low doses of MDMA showed increased social interaction and decreased aggressive behavior while the drug is still 'on board' (Morley and McGregor, 2000), whereas 5-HT-depleting doses of MDMA produced later increases in aggressiveness in the social interaction test (Ando et al, 2006), though not in the resident-intruder paradigm (Kirilly et al, 2005). When the social interaction test was carried out in the present study, many of the control (SAL/SAL) rats fought when confronted with an unfamiliar male, whereas the animals in the SAL/MDMA group unexpectedly showed significantly less of this behavior.…”
Section: Discussionsupporting
confidence: 55%
“…Although several reports have associated MDMA and aggressive behavior [64], a single administration of MDMA in rats was shown not to affect aggression after 3 weeks [65], although chronic intermittent administration of MDMA during adolescence reduced social behavior and aggression in adult mice [24]. In line with the present results, Wallinga et al [64] reported an increase in aggression 23 days after chronic MDMA treatment only in low aggressive and not in medium or high aggressive rats.…”
Section: Anxiety Profile and Social Behaviorssupporting
confidence: 87%
“…This is consistent with the existing evidence indicating that acute ecstasy intoxication may reduce aggression (Curran et al, 2004;Kirilly et al, 2006;Machalova et al, 2012). My findings build on previous research by indicating that even when combined with alcohol ecstasy still does not appear to be associated with aggression.…”
Section: Antisocial Behaviour: Concurrent and Simultaneous Alcohol Ansupporting
confidence: 91%
“…Preclinical studies have shown MDMA to cause a dose-dependent reduction in aggression (Kirilly et al, 2006;Machalova, Slais, Vrskova, & Sulcova, 2012). Reductions in selfreported aggression during ecstasy intoxication have also been reported in human studies (Curran, Rees, Hoare, Hoshi, & Bond, 2004).…”
Section: Ecstasy and Aggressionmentioning
confidence: 86%
See 1 more Smart Citation